1980, année difficile - Parizeau, Gérard (Assurances, 1981)
Each year, our editor summarizes the main events which took place during the preceding twelve months. Based on approximate figures, he mentions this year the results obtained in the general insurance field, as well as in the life and re-insurance markets, together with the problems which the industry has had to solve, either partially or entirely. In the general insurance industry, the main problem is the cost of claims which is too high, compared with insurance rates that have not been increased during the last two or three years. Although in a better position generally, life insurance has its own difficulties and accomplishments which are interesting to know in a period of extreme instability. The author mentions new coverages as a source of activity and resourcefulness.